PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KORUPSI BERBASIS SIBER DI INDONESIA - Doni Sabdan Tanjung; Suci Ramadani; Briski Viktor H. Sinaga; Derta Simbolon (Berajah Journal, 2026)
The development of information and communication technology has significantly transformed government administration systems, particularly through the implementation of electronic systems such as e-procurement, e-budgeting, and various other digital services. However, alongside these advancements, new forms of corruption have emerged that utilize cyber means as both the primary and supporting tools in committing unlawful acts. This study aims to analyze the legal framework, criminal liability, and effectiveness of law enforcement concerning cyber-enabled corruption crimes in Indonesia. The research method employed is normative legal research using statutory, conceptual, and case approaches. The findings indicate that Indonesian law has not explicitly regulated cyber-based corruption as a distinct offense; therefore, law enforcement is still conducted through a cumulative application of the Anti-Corruption Law, the Electronic Information and Transactions Law, and other related regulations. Criminal liability is not limited to public officials but also extends to other parties involved in the use of electronic systems to facilitate corruption. The effectiveness of law enforcement still faces obstacles such as regulatory limitations, inadequate human resources, and the complexity of digital evidence. Therefore, regulatory harmonization and strengthening the capacity of law enforcement agencies are necessary to address corruption crimes in the digital era effectively.